Pengembangan Kompetensi Aparatur Sipil Negara: Analisa Peluang Penerapan Datasering di Kementerian Agraria dan Tata Ruang/ Badan Pertanahan Nasional - adinegoro, kurnia rheza randy (Puslatbang KHAN, 2024)
This study aims to analyze the opportunities and potential for implementing the detasering system at the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). Detasering is a method of human resource management that aims to improve the efficiency and effectiveness of public services that allow employees to be assigned to a particular place and/or work unit for a certain period of time as a means to exchange experiences and broaden the direction of views. This study uses a qualitative descriptive approach with data collection through literature studies and analysis of related documents. SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis will be used to provide opportunities and challenges related to the implementation of detasering at ATR/BPN. In addition, this study will also consider the experience of other government institutions that have implemented detasering as a reference in understanding the potential for successful implementation. The results of this study are expected to provide a comprehensive view of the opportunities and benefits that can be obtained by ATR/BPN through the implementation of detasering. In addition, this study will also discuss potential obstacles that may be faced in the implementation process, as well as provide strategic recommendations to maximize the effectiveness of detasering at this institution. Thus, this research can provide an important contribution in efforts to improve the human resource management system and public services in the agrarian and spatial planning sectors in Indonesia.